Population and economic growth: Ancient and moderns - Elise S. Brezis; Warren Young (Bar-Ilan University, Department of Economics, 2013)
This paper focuses on the evolution of the relationship between population and economic growth from Hume to New Growth Theory. In the paper, we show that there were two main views on the subject. There were those who assumed that the relationship between fertility rates and income was positive. On the other hand, there were those who raised the possibility that this linkage did not occur, and they emphasized that an increase in income did not necessarily lead to having more children. The paper will show that their position on the issue was related to a socio-economic fact: the sibship size effect. We show that those who took the view that an increase in income leads to the desire to have more children, did not take into consideration a sibship size effect, while those maintaining that there existed a negative relationship, introduced into their utility function a sibship size effect.
Keywords: B10; D10; J13; 330; population; economic growth; Sibship size effect; children; fertility rates